Effect of Soaking Time Using Petroleum Ether on the Feather Morphology of Native Chicken - Darjito, Darjito; Tjahjanto, Rachmat T.; Mutrofin, Siti; Sinambela, Lopian S. P. (Indonesian Green Technology Journal, 2025)
The process of extracting keratin from chicken feathers needs to be treated initially to remove some of the compounds that can reduce the extraction results. Petroleum ether can serve as a degreaser in the initial process of washing. This study focuses on the effect of the long time of soaking the feathers of free-range chickens with petroleum ether on the soxhlet process with different time variations on the change in mass and morphological changes of the feathers of free-range chickens. In this study, several stages were carried out, namely (1) Washing chicken feathers using liquid detergent, (2) Washing chicken feathers using acetone, and (3) Washing chicken feathers using petroleum ether with varying soaking times. The results of the 3 stages of washing the feathers of free-range chickens can change the morphology of chicken feathers from rough black to bright gray with soft texture and the influence of the soaking time using petroleum ether is that the longer the soaking time, the greater the shrinkage value of the chicken feathers studied.